OCCUPATIONAL ATTRIBUTES AND ITS IMPACT ON HEALTH AMONG TEA PLUCKING WOMEN WORKERS OF ASSAM - D. KALYANI* (The Journal of Research ANGRAU, 2023)
The study examined the socio-economic background, working circumstances, and potential health effects of the women who pluck tea leaves in Assam state. A sample of 100 tea plucking women workers were selected by using random sampling method from Dibrugarh and Jorhat districts, Assam. The data was collected between April and June 2021. The tea plucking women were low waged full - time employees, who got RS.1160 per week as their wage. Most of the respondents (82%) plucked more than 20 kg of tea leaves per day, whereas 56 percent of the respondents plucked tea leaves below 20 kg. A total of 69 percent of the respondents used basket along with other personal protective equipments while plucking tea and 31% of them plucked tea leaves only with a basket. While Majority of the tea plucking women workers (63%) had problem with the basket due to its transportation issue, 94 percent of the women workers had body pain during and after their work because they have to stand all day in work with a heavy basket full of tea leaves.